2016
DOI: 10.1097/mib.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody Against Triggering Receptor Expressed on Myeloid Cells 1 (TREM-1) Dampens Proinflammatory Cytokine Secretion by Lamina Propria Cells from Patients with IBD

Abstract: An anti-TREM-1 antibody can dampen secretion of proinflammatory cytokines in inflamed patients with elevated PGLYRP-1. Moreover, PGLYRP-1 + myeloperoxidase is a potential biomarker for predicting the effect of anti-TREM-1 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…TREM-1 activation leads to the secretion of pro-inflammatory cytokines and chemokines such as TNF, IL-6, IL-1β, IL-8 and CCL2, and synergizes with TLR activation (251)(252)(253)(254). Our group and another showed that intestinal mature Mfs expressed less TREM-1 than immature Mfs and blood monocytes (253,255), which has been corroborated by a recent study using scRNA-Seq (228) (Figure 6). The decrease of TREM-1 expression during Mf maturation seems to be due to the intestinal anti-inflammatory microenvironment, as monocytes cultured in the presence of IL-10 and TGF-β have reduced TREM-1 expression (253).…”
Section: Function Of Intestinal Mucosa Macrophagessupporting
confidence: 85%
See 3 more Smart Citations
“…TREM-1 activation leads to the secretion of pro-inflammatory cytokines and chemokines such as TNF, IL-6, IL-1β, IL-8 and CCL2, and synergizes with TLR activation (251)(252)(253)(254). Our group and another showed that intestinal mature Mfs expressed less TREM-1 than immature Mfs and blood monocytes (253,255), which has been corroborated by a recent study using scRNA-Seq (228) (Figure 6). The decrease of TREM-1 expression during Mf maturation seems to be due to the intestinal anti-inflammatory microenvironment, as monocytes cultured in the presence of IL-10 and TGF-β have reduced TREM-1 expression (253).…”
Section: Function Of Intestinal Mucosa Macrophagessupporting
confidence: 85%
“…As described above, TREM-1 is an inflammationamplifying receptor expressed on myeloid cells; it is involved in immune responses triggered by bacteria (249,250), yet its role in IBD is poorly understood. Our group showed that an anti-TREM-1 antagonist antibody dampened secretion of several proinflammatory cytokines and chemokines by LP cells from highly inflamed intestinal mucosa of IBD patients (255), supporting a potential role of TREM-1 in perpetuating intestinal inflammation in IBD patients.…”
Section: Function Of Intestinal Mucosa Macrophagesmentioning
confidence: 55%
See 2 more Smart Citations
“…Peptidoglycan recognition protein -1 (PGRP-1) only or linked to its ligand -peptidoglycans (PG) 40 was found to induce TREM-1 signaling and the synergetic interaction with TLRs 41,42 [43][44][45] .…”
Section: Trem-1 Ligandsmentioning
confidence: 99%